The relationship between mental health and athletes' readiness after ACL injuries among football players - Nuryasmin, Faten; Abidin, Muhammad Amrun Haziq; Adnan, Aizzat; Linoby, Adam; Sazali, Razif; Zulqarnain, Muhammad; Md Yusoff, Yusandra (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates the mental health status of 35 professional and collegiate football athletes, aged 18–30, during ACL rehabilitation to determine how psychological symptoms relate to their readiness to return to competition. By analyzing levels of depression, anxiety, and stress alongside ACL-RSI scores, the research identifies correlations between mental well-being and the psychological confidence required to resume high-impact play. The findings offer critical insights into the relationship between psychological recovery and physical rehabilitation, aiming to improve support systems for injured athletes navigating the transition back to sport.